Enhancing Students' Turning Machining Competence through Project-Based Blended Learning - M.Balya Firjon Barlaman; Ari Dwi Nur Indriawan Musyono (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2026)
This study aims to explore the implementation and impact of project-based blended learning in improving lathe machining competence among students at SMK Negeri 5 Semarang. A quantitative approach with a quasi-experimental method and nonequivalent control group design was used. The research subjects included two classes: an experimental class applying project-based blended learning and a control class using conventional methods. Data were collected through pretests and posttests and analyzed using normality, homogeneity, and simple linear regression tests. The results showed a significant improvement in student competence after the implementation of the blended learning method, with the experimental class's average score increasing from 74.38 to 81.16. This research contributes to the development of technical education by offering an effective instructional model that integrates theoretical and practical learning. The findings indicate that the integration of technology and real-world projects in vocational education enhances students' technical skills and workforce readiness.